Criminal Offenses of Misuse of Deepfake Porn Technology Based on Indonesia's Positive Law - Siti Nur Azizah; Zaid Alfauza Marpaung (Warmadewa Press, 2024)
This study aims to analyze the adequacy of Indonesia's positive law in addressing the criminal offenses related to the misuse of deepfake porn technology. As information and communication technology continues to advance significantly, many people utilize these technological developments for beneficial purposes. However, these advancements have also contributed to the rise of new forms of cybercrime, such as deepfake porn a manipulated video or photo containing pornographic content. The normative juridical technique used in this study includes secondary data analysis and literature review. Despite laws targeting the use of pornographic content on websites, such as the Criminal Code, Law Number 44 of 2008 on Pornography, Law Number 27 of 2022 on Personal Data Protection, and Law Number 1 of 2024 (Second Amendment to Law Number 11 of 2008 on Information and Electronic Transactions), the findings show that Indonesia's current legal framework is insufficient to effectively prosecute deepfake porn offenders. The absence of precision in these legal laws regarding deepfake porn reveals serious weaknesses in the criminal law policy of the nation.